FORMULATION AND TESTING OF ANTIBACTERIAL ACTIVITY OF FACIAL TONER PREPARATIONS CHINESE BELT LEAF EXTRACT (Peperomia pellucida L. Kunth) AGAINST THE BACTERIA Propionibacterium acnes - Nasikin, M. Ali; Ridlo, Achmad; Rakhmayanti, Regia Desty; Hapsari, Azizah Nur (Journal of Local Therapy, 2024)
Abstract: Chinese betel leaf (Peperomia pellucida L.Kunth) is a herbal plant that can be used to treat abscesses, acne, boils and skin inflammation. Chinese betel leaves contain chemical compounds including alkaloids, flavonoids, saponins, tannins and triterpenoids which can inhibit the growth of Propionibacterium acnes bacteria. The Chinese betel leaf extract content can be used as a refreshing toner, especially for dry and acne-prone skin. The aim of this research is to determine the results of physical quality tests and antibacterial activity of Chinese betel leaf extract facial toner formulations with an additional active ingredient concentration of 7.5%; 15% and 30%. This type of research is experimental research with a descriptive research design. The organoleptic test results of the base are clear and odorless, while the other 3 formulas are brownish green in color, have a distinctive aroma of Chinese betel leaf extract and are in liquid form. The homogeneity test results of the preparation are homogeneous. F0 pH test results 6.327; FI 5.344; FII 5,243 and FIII 5,067. Viscosity test results F0 5.32 cps FI 6.34 cps and FII 6.33 cps. The results of the antibacterial activity test F0, FI, FII, and FIII were respectively 0.00 mm, there was no inhibition zone, 7.37 mm, 13.35 mm, 16.24 mm and in the positive control clindamycin it was 21.17 mm. Based on the results of the physical quality test and antibacterial activity of the toner preparation, the toner preparation has met existing quality standards so it is safe to use and the toner preparation with the strongest antibacterial activity is found in FIII.